Case Report: Biallelic BRCA1 pathogenic alterations in a Fanconi Anemia patient and clinical implications of variant location - Young, Colin C.; Lahr, Ashley; Nestor, Caroline; Kaminski, Ashley; Richardson, Marcy E.; Arnold, Georgianne L. (Frontiers in Oncology, 2025)
Pathogenic alterations in BRCA1 are associated with autosomal dominant breast and ovarian cancer and autosomal recessive Fanconi Anemia Subtype S (FA-S). FA-S accounts for <1% of all reported cases of FA with only ten patients identified in the literature to-date. Here we describe an eleventh FA-S proband with severe microcephaly, growth failure, duodenal stenosis, hyperpigmented macules, dysmorphic features, and abnormal chromosomal breakage, consistent with other FA-S patients. Two pathogenic BRCA1 variants (c.191G>A, p.C64Y and c.3991C>T, p.Q1331*) were identified in trans. At four years old, this patient has not been diagnosed with cancer or bone marrow failure, which are hallmark features in other subtypes of FA. Like a majority of the literature-reported FA-S patients, this patient harbors a truncating variant in BRCA1 exon 11. This exon undergoes alternative splicing resulting in a protein with partial BRCA1 activity. The retained activity may be enough to rescue an otherwise lethal phenotype explaining the viability of FA-S patients. This retained functional activity may also modify clinical cancer risks and treatment implications for heterozygous carriers of exon 11 truncating variants. This work further characterizes the features of FA-S patients and discusses a molecular hypothesis for the rarity and viability of individuals with this condition.